Hubungan Indeks Massa Tubuh dengan kadar HDL pada pasien Diabetes Mellitus tipe 2 - Mitta Fidyana; Firhat Esfandiari; Esteria Maharyuni; Muhammad Nur (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Diabetes mellitus type 2 is a metabolic disease characterized by an increase in insulin released by pancreatic beta cells and / or insulin resistance. Excessive nutrition with excess body fat accumulation increases the risk of suffering from degenerative diseases. The purpose of this study was to study whether there was a relationship between Body Mass Index with HDL levels in patients with type 2 Diabetes Mellitus FKTP patients at the Independent Practitioner Doctor K. Hakikiyah, Lampung Tengah in 2019. This research method used observational analytic with cross sectional design. The sampling technique in this study used the total sampling quota method with a total sample of 56 people collected. Data analysis using Pearson trial. The highest BMI was the excess BB category by 33 people (58.9%), the highest HDL frequency distribution, namely the Low category by 29 people (51.8%), and obtained (p-value = 0.034 and r = -0.284 Related to Body Mass Index with HDL levels having a weak direction and a negative direction, is if BMI increases, HDL levels increase and vice versa.